Pengembangan Virtual Laboratory Biologi Pada Praktikum Uji Golongan Darah - Ajeng Pramita; Indayana Febriani Tanjung; Siti Maysarah (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2023)
This study aims to determine the results of the development, measure the feasibility and response of students from the Biology Virtual Laboratory in the Blood Type Test Practicum. Research and Development (R&D) is the method used in this study. With eight stages of the Sugiyono method, namely the first stage is the initial stages of potential and problems up to the final product. August-November 2021 the implementation of this research used 35 samples of class XI students. This study used a questionnaire instrument from 3 experts, namely material experts, media experts as well as field practitioners and 35 students. This study obtained the percentage results from material experts 93% with a very appropriate category, based on media experts 93% with a very feasible category, and field practitioners (Biology teachers) with a percentage of 92%. As for the results of the students' responses, they obtained a score of 90% with a very feasible category, so it can be concluded that the Biology Virtual Laboratory is suitable for use in practicum activities for blood type testing.